POLITICS OF LAW OF RISK MANAGEMENT APPLICATION IN THE MANAGEMENT OF THE STATE-OWNED ENTERPRISES IN INDONESIA - Prasetio, . (Yustisia, 2018)
Risk management within the State-Owned Enterprises (SOEs) is formally regulated; however, risk-conscious cultures have not been seen as strategic needs. Orientation on opportunity, profit growth, and market share still dominate decision making. Risk management is still often considered to hamper the process and slow growth. Risk awareness values are considered important to build and entrenched in an ongoing system so that risk awareness is internalized in every decision-making process. The following descriptions are based on literature studies and empirical experiences the authors describe the ideas and experiences of introducing and building risk awareness culture in the environment of state enterprises in the early stages. UU NO. 1 of 2003 on SOEs does not regulate in detail about risk management on SOEs. The existence of risk management is contained in the Regulation of the Minister of SOE numbered PER-09 / MBU / 2012. This regulation contains amendments to Article 12 paragraph 10 PER-01 / MBU / 2011 concerning the implementation of Good Corporate Governance in State-Owned Enterprises, and is regulated in more detail at the Decree of the Secretary of the Ministry of SOEs No. SK-16 / S.MBU / 2012 on the assessment indicators / parameters and Evaluation of Good Corporate Governance Implementation on SOEs. The legal politics that exist despite their existence, but lacks a strong philosophical meaning because the rules are not supported in detail in regulation at the level of law.